PERTANGGUNG JAWABAN TERHADAP NASABAH PENGGUNA INTERNET BANKING - Eka Grata Saputra, I Gst Ngurah; Sukeni, Ni Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013)
Internet banking is a technological exploiting of internet as media to dosome banking transaction.In daily practice, often happened trouble into form of technical trouble or typical trouble which is harming the internet banking customer.Therefore,in this journal will be described about the disturbances that occurred in the internet banking. And also describe about the responsibility of the trouble which is happen on internet banking uses, forms of accountability seen which party made a mistake and completion is done by litigation or alternative dispute resolution.
Keywords: Internet Banking, Disturbances, Responsibility